Prognostic value of perioperative red blood cell transfusion and anemia on survival and recurrence in oral squamous cell carcinoma. (August 2020) - Spanier, Gerrit; Böttcher, Janika; Gerken, Michael; Fischer, René; Roth, Gabriel; Lehn, Petra; Klingelhöffer, Christoph; Meier, Johannes K.; Fraccaroli, Alessia; Tischer, Johanna; Ettl, Tobias; Klinkhammer-Schalke, Monika; et al.
Highlights: Preoperative anemia is a negative predictor on survival and recurrence in OSCC. Same for perioperative red blood cell transfusion (RBT) in a dose-dependent manner. Unfavourable effects are mainly seen in perioperative RBT of non-anemic patients. Transfusion strategy should be adapted depending on anemia status in OSCC patients. Abstract: Objective: To evaluate the prognostic effect of allogenic red blood cell transfusion (RBT) and preoperative anemia in patients with oral squamous cell carcinoma (OSCC) undergoing primary tumor resection. Methods: We retrospectively analyzed a cohort of 621 patients, diagnosed with OSCC receiving tumor resection in curative intention. Preoperative anemia and perioperative RBT were evaluated according to WHO definition. Overall survival (OAS) as well as recurrence-free survival (RFS) was evaluated in transfused and non-transfused as well as in anemic and non-anemic patients. In addition, outcome parameters were calculated for distinct amounts of perioperatively administered RBTs. Data analysis was performed by uni- and multivariate statistics. Mean follow-up time was 7.3 years. Results: Preoperative anemia was diagnosed in 29% of OSCC patients. Anemic patients displayed a significantly decreased five-year OAS (44%) in comparison to non-anemic equivalents (69%). 70% of non-transfused OSCC patients were alive after five years, whereas in case of RBT five-year OAS was 41%. These findings were substantiated by subgroup analysis in patients without preoperative anemia. For anemic patients however, no deleterious effect on survival in case of perioperative RBT was seen. Increasing numbers of received RBTs were shown to worsen outcome of OSCC patients in a dose-dependent manner. Conclusion: Preoperative anemia and RBT are significantly associated with impaired long-term outcome of patients suffering from OSCC. Future studies are needed to evaluate differentiated effects of RBTs in anemic and non-anemic OSCC patients and accordingly providing individual transfusion strategies to ameliorate outcome of patients suffering from OSCC.